The Role of Technology in Building Competitive Advantage in the Digital Age in Indonesia - Setyadi, Yusuf; Aziz, Abdul; Rucita, Nina; Putra, Irwansyah; Wiboyo, Kukuh; Sugiarto, Imam (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
This paper explores the role of technology in building competitive advantage in the digital era through a case study on Tokopedia, one of the largest e-commerce platforms in Indonesia. Tokopedia has implemented various advanced technologies such as big data, analytics and the like to improve operational efficiency, customer experience, and product innovation. The impact of this technology adoption includes increased sales, user conversion, customer satisfaction, as well as cost efficiency and operational time. Recommendations for Tokopedia include continuing to innovate with advanced technology, optimizing customer experience, improving security and reliability, developing a digital ecosystem, utilizing big data for decision-making, and expanding markets. This paper shows that technology plays an important role in maintaining and increasing competitive advantage in the highly competitive e-commerce industry.